Unusually large magnetic moment and tricritical behavior of the CMR compound NaCr2O4 revealed with high resolution neutron diffraction and SR - Elisabetta Nocerino; Ola Kenji Forslund; Hiroya Sakurai; Akinori Hoshikawa; Nami Matsubara; Daniel Andreica; Anton Zubayer; Federico Mazza; Takashi Saito; Jun Sugiyama; Izumi Umegaki; Yasmine Sassa; et al. (JPhys Materials, 2023)
The mixed valence Cr ^3+ /Cr ^4+ compound NaCr _2 O _4 , hosts a plethora of unconventional electronic properties. In the present study, muon spin rotation/relaxation ( $μ^+$ SR) and high-resolution time-of-flight neutron powder diffraction measurements were carried out on high-quality samples to clarify the complex magnetic ground state of this unique material. We identified a commensurate canted antiferromagnetic order (C-AFM) with a canting angle of the Cr spin axial vector equal to $θ_{c} = (8.8±0.5)^{°}$ , and an estimated Cr moment $μ^{C}_{Cr} \sim (4.30±0.01)μ_B$ . Such an unusually large value of $μ^{C}_{Cr}$ is compatible with the existence of high-spin Cr sites created by the presence of an unconventional negative charge transfer state in NaCr _2 O _4 . In addition to the C-AFM structure, a novel magnetic supercell was also revealed. Such supercell display an incommensurate (IC)-AFM propagation vector (0 0 ${\textstyle \frac{1}{2}-}δ$ ), having a Cr moment $μ^{IC}_{Cr} = (2.20±0.03)μ_B$ . It is suggested that the C-AFM and IC-AFM modulations have two different electronic origins, being due to itinerant and localized contributions to the magnetic moment respectively. Finally, the direct measurement of the magnetic order parameter for the C-AFM structure provided a value of the critical exponent $β = 0.245 ≈ \frac{1}{4}$ , suggesting a non conventional critical behavior for the magnetic phase transition in NaCr _2 O _4 .